2017
DOI: 10.1590/1983-40632016v4747576
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and sanitary quality of soybean seeds harvested at different periods and submitted to storage1

Abstract: Delayed harvesting may affect the physiological quality of soybean seeds, due to adverse conditions in the field. This study aimed to evaluate the physiological and sanitary quality of soybean seeds (BRS 820 RR® cultivar) harvested at eight periods (0; 5; 10; 15; 20; 25; 30; and 35 days after the R8 phenological stage - full maturity) and stored for two periods (0 and 8 months). The following evaluations were carried out: moisture content, germination and emergence rate, emergence speed index, total plant dry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 13 publications
(13 reference statements)
0
20
1
2
Order By: Relevance
“…However, Carvalho et al (2014) observed that not necessarily seeds of soybean cultivars with higher lignin contents show higher physiological quality. Zuffo et al (2017a) report that the germination potential tends to decrease as the seeds remain in the field after physiological maturity, a fact that did not occur in this study. However, these authors allowed a greater exposure time to the climatic storms, since seeds remained in the field until the 10 days after the reproductive R8.…”
Section: Resultscontrasting
confidence: 57%
“…However, Carvalho et al (2014) observed that not necessarily seeds of soybean cultivars with higher lignin contents show higher physiological quality. Zuffo et al (2017a) report that the germination potential tends to decrease as the seeds remain in the field after physiological maturity, a fact that did not occur in this study. However, these authors allowed a greater exposure time to the climatic storms, since seeds remained in the field until the 10 days after the reproductive R8.…”
Section: Resultscontrasting
confidence: 57%
“…Regarding seed sanity, the pathogens Colletotrichum sp., Phomopsis sp., Penicillium sp., Aspergillus sp., Fusarium sp., Semitectum sp., Cercospora kikuchii, and Alternaria sp were detected. These pathogens were also observed by Zuffo et al (2017a) in soybean seeds harvested at different times. Pathogens observed in the seeds of this study are the species of higher occurrence in Brazil; they cause significant production losses and decrease the seed quality of soybean (DANELLI et al, 2011).…”
Section: Source Of Variationmentioning
confidence: 78%
“…Seeds from plants sprayed with saflufenacil and grammoxone showed no statistical difference about harvest times. Diniz et al (2013a) and Zuffo et al (2017a) verified a higher incidence of Colletotrichum sp., Phenopsis sp., Penicillium sp., Aspergillus sp., Fusarium sp., Semitectum sp., Cercospora kikuchii, and Alternaria sp. in seeds harvested at 15 days after the R 8 stage.…”
Section: Source Of Variationmentioning
confidence: 91%
“…However, the intensity of these negative effects depends on the time that seeds remain in the field, genotype and climatic conditions, such as temperature and rainfall. The decrease of soybean seed quality in the field involves physical, chemical and physiological changes, as well as damage caused by microorganisms (Zuffo et al 2017). Minuzzi et al (2010) concluded that the highest seed quality can be obtained by performing the harvest at 7 days after the physiological maturity.…”
Section: Abstract Resumomentioning
confidence: 99%